Remote Sensing Method for Determination of Industry Pollution Sites - Aliyeva , E.N. (Herald of Azerbaijan Engineering Academy, 2023)
The advantage of the textural feature over the NDVI index in solving the issue of remote recognition of open landfills and buried wastes is noted. A texture-spectral method for remote recognition of landfill sites is developed, where the spectral feature is used to validate the results obtained from the texture feature. It is established that it is expedient to perform textural feature recognition by such intervals of values of the average signal of black-and-white orthophoto images, the value of which is not less than two times the standard deviation of the noise signal.